Sosialisasi Pencegahan Kekerasan Dalam Rumah Tangga Di Desa Mojokusumo, Kemlagi, Mojokerto - Moh. Kamaluddin; Akramin Dirgantara Perkasa; Anandhyta Dewi N.K; Dina Ayu Agustin; Eka Purwaningtyas; Hana Nur Aini; Hanifah Nur Fadlilah; Hetta Prisca Meica Tosya; Insanul Lazim; Kusar Yanti; Meila Fatma Nuaji; Moch Ferdinan P.P.S; Mochtar Ade Zakaria; Muhammad Khotibul Umam; Nur Rahmawati Vivi Shokhifah; Rizki Herdiansyah; Ruli Astutik; Sasmita Dwi Novitasari; Silvia Margareta; Singge Prastiyo; Wahyu Tri Andi Hidayat; Wiyogo Purnomoadji; Yudhatama Bagu Rizkyanto; Yusuf Pujianto; Zilminas Nizarisma Afriza (Jurnal Nusantara Berbakti, 2024)
The Act No. 23 of 2004 on the Elimination of Domestic Violence refers to behaviour directed at individuals, especially women, which results in both physical, sexual, psychological and domestic suffering. Threats involve acts, coercion, or restrictions of freedom that are also considered to be illegal in the household environment. With the enactment of the KDRT Act, the perpetrators of these crimes are no longer subject to the articles contained in the Criminal Law Book (KUHP), but are regulated by the KDRT Act which gives more severe criminal sanctions because of their special nature. With the aim of providing understanding to the public, especially through the law enforcement activities on domestic violence, KKN students of Mayjen Sungkono University in 2023 participated in the implementation of this activity. This socialization aims to improve understanding of the behaviour that falls within the category of DRC and its negative impact on society. Through this socialization, it is expected that the public will understand that Domestic Violence (DDRT) is a criminal act, as well as understand how to settle it through out-of-court paths before entering the realm of formal justice.